Contribution of Api-Nampa Conservation Area on the Livelihood of Poor and Disadvantaged People of Darchula District, Nepal - Shakya, Bimal; Pant, R.R. (Himalayan Biodiversity, 2017)
The study was carried out in the community forests of Latinath and Khandeswori Village Development Committees (VDCs) of Api-Nampa Conservation Area, Nepal. The life style in the area is very primitive and close to nature and the area has diverse forest and ecosystem that provide diverse habitat for wildlife. The study demonstrates that, among the five capitals assessed, the condition of financial capital is the worst where as that of physical capital is the best. The condition of other three capitals (Human, Social and Natural) is satisfactory. The findings of this research conclude that the conservation area has played a significant role in livelihood upliftment of the people in the study area. It may have been too early to draw this conclusion as the conservation area was established only in 2010, however, the studied community forests have been used since last fifteen years. Fuel wood is an exclusive source of cooking fuel in both the VDCs. Demand and supply gap of fuelwood in Khandeswori VDC is comparatively higher because the huge amount of fuelwood is used for heating purpose in the winter. The insufficient supply from the community forest compels the locals to use the nearby conservation area forest to meet up with the need.